Genomics-Guided Exploitation of Lipopeptide Diversity in Myxobacteria - Burgard, Christian; Zaburannyi, Nestor; Nadmid, Suvd; Maier, Josef; Jenke-Kodama, Holger; Luxenburger, Eva; Bernauer, Hubert S; Wenzel, Silke C (ACS Chemical Biology, 2017)
Analysis of 122 myxobacterial genome sequences suggested 16 strains as producers of the myxochromide lipopeptide family. Detailed sequence comparison of the respective mch biosynthetic gene clusters informed a genome-mining approach, ultimately leading to the discovery and chemical characterization of four novel myxochromide core types. The myxochromide megasynthetase is subject to evolutionary diversification, resulting in considerable structural diversity of biosynthesis products. The observed differences are due to the number, type, sequence, and configuration of the incorporated amino acids. The analysis revealed molecular details on how point mutations and recombination events led to structural diversity. It also gave insights into the evolutionary scenarios that have led to the emergence of mch clusters in different strains and genera of myxobacteria.